New Strait Times, 9 May 2010 - Cruez, Annie Freeda (The New Straits Times Press (M) Bhd, 2010)
Matron Zainab Abdullah, 53, of Sultanah Aminah Hospital was on cloud nine when she graduated in biomedical and health sciences last November.